Comparative Analysis of Functional Capacity Improvements Through 6MWD Testing Across Different Respiratory Conditions: Implications for Targeted Pulmonary Rehabilitation - Chacko, Sneha; Shah, Gaurang (International Journal of Pharmaceutical Investigation, 2026)
Background The 6-Min Walk Distance (6MWD) test is widely used to assess functional capacity in respiratory patients, but response patterns across different respiratory conditions remain poorly understood. Materials and Methods 115 patients (29 Asthma, 46 COPD, 40 ILD) underwent 6MWD testing before and after pulmonary rehabilitation. Changes in distance, heart rate, and oxygen saturation were analyzed across diagnostic groups. Results Mean 6MWD improved from 363.90 m to 375.26 m post-rehabilitation. Asthma patients showed the most significant improvement (30 m increase), followed by COPD (8 m increase), while ILD patients showed minimal change. Heart rate and SpO2 changes during testing showed no significant differences pre- and post-rehabilitation (p>0.05). Diagnostic category significantly influenced improvement patterns (p<0.05). Conclusion The effectiveness of pulmonary rehabilitation on functional capacity varies significantly across respiratory conditions, with asthma patients showing the most marked improvements. These findings suggest the need for condition-specific rehabilitation protocols and indicate that 6MWD improvements may not be a universally appropriate primary outcome measure across all respiratory conditions.
Keywords: 6MWD; Pulmonary Rehabilitation; Asthma; COPD; ILD